2019
DOI: 10.1038/s41586-019-0889-9
|View full text |Cite
|
Sign up to set email alerts
|

Global environmental consequences of twenty-first-century ice-sheet melt

Abstract: If citing, it is advised that you check and use the publisher's definitive version for pagination, volume/issue, and date of publication details. And where the final published version is provided on the Research Portal, if citing you are again advised to check the publisher's website for any subsequent corrections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
422
1
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 367 publications
(445 citation statements)
references
References 123 publications
21
422
1
1
Order By: Relevance
“…There is, for example, no addition of melt water from ice sheets in either of them even though there is considerable warming in both of them. Recent research has shown a strong influence of melt water forcing on the transient evolution of coupled climate models (Golledge et al 2019). We will come back to what distinguishes these two branches in terms of changes in the general circulation in the discussion and conclusions section.…”
Section: Resultsmentioning
confidence: 95%
“…There is, for example, no addition of melt water from ice sheets in either of them even though there is considerable warming in both of them. Recent research has shown a strong influence of melt water forcing on the transient evolution of coupled climate models (Golledge et al 2019). We will come back to what distinguishes these two branches in terms of changes in the general circulation in the discussion and conclusions section.…”
Section: Resultsmentioning
confidence: 95%
“…In the left panel, g* and g** refer to two interpretations of the Coupled Model Intercomparison Project Phase 5 ensemble uncertainty (see Le Bars et al, 2017). loss are much higher than those of other recent publications (Golledge et al, 2015;Levermann et al, 2014;Ritz et al, 2015), because their model produces widespread early surface melting of ice shelves, leading to hydrofracturing and complete collapse (as occurred for the Larsen B ice shelf in 2002), and subsequent marine ice cliff instability (MICI) in many places. While this is physically plausible, this chain of processes has so far not been observed, and the most recent publications Golledge et al, 2019) find a much smaller Antarctic contributions by 2100 as well as that it is not essential that the ice cliff mechanism is required to simulate paleo sea level observations. For those regions where Antarctica is currently retreating (Thwaites glacier in particular), the general understanding is that it is not due to the above mentioned chain of processes but rather due to enhanced basal melting below the ice shelves (Joughin et al, 2014;Rignot et al, 2014).…”
Section: /2018ef001071mentioning
confidence: 94%
“…Very low confidence: Third, we combine the probability distributions of studies based on DP16, notably Kopp et al (2017) and Le Bars et al (2017). We assign a very low confidence to these studies due to their results being conditional on a single and observationally poorly constrained line of evidence (i.e., a single ice sheet model), and the much lower projections from the most recent studies Golledge et al, 2019).…”
Section: /2018ef001071mentioning
confidence: 99%
“…Understanding past changes is critical in order to improve projections of Antarctic ice sheet evolution over the next decades and centuries in response to climate change. Previous modeling studies showed variable Antarctic contribution to sea level rise over the coming century, depending on the physical processes included (e.g., Edwards et al, 2019), forcing used (e.g., Golledge et al, 2015;Schlegel et al, 2018) or model parameterizations (e.g., Bulthuis et al, 2019), leading to results varying between a few mm to more than 1 meter of sea level contribution by the end of the century (Ritz et al, 2015;Pollard et al, 2015;Little et al, 2013;Levermann et al, 2014). Model intercomparison efforts such as Ice2Sea (Edwards et al, 2014) and SeaRISE 35 (Sea-level Response to Ice Sheet Evolution, Bindschadler et al, 2013;Nowicki et al, 2013a) highlighted the large discrepancies in numerical ice flow model results, even when similar climate conditions are applied for model forcing.…”
mentioning
confidence: 99%